Production of methyl levulinate from cellulose over cobalt disulfide: The importance of the crystal facet (111). (March 2022) - Gao, Wenran; Wu, Gang; Zhu, Xun; Asif Akhtar, Muhammad; Lin, Guiying; Hu, Xun; Huang, Yong; Zhang, Shu; Zhang, Hong
Graphical abstract: The crystal facet (111) of CoS2 is effective for the conversion of cellulose to methyl levulinate. Highlights: The ML yield from cellulose reaches 61 mol% under the tested conditions. The crystal facet (111) of CoS2 is responsible for conversion of cellulose to ML. Surface Co 2+ species plays an important role in catalytic performance of CoS2 . The activity of crystal facet can be reflected by the calculated work functions. Abstract: The conversion of cellulose to platform chemicals has attracted much attention because of its renewability. This work proposed an earth-abundant cobalt disulfide as a heterogeneous catalyst for methyl levulinate production from cellulose. The highest yield of methyl levulinate reached 61 mol% under the tested conditions of 200 °C, 2 MPa initial pressure, 0.45 catalyst/cellulose mass ratio, and 3 h reaction time. The XRD and TEM analyses demonstrated the crystal facet (111) of cobalt disulfide as a robust active site, which was in good agreement with the highest acidity of the crystal facet (111) calculated by the work functions. The XPS characterization showed that the main chemical valence of cobalt disulfide responsible for the methyl levulinate production was the surface Co 2+ species. This study is valuable for the development of a recoverable catalyst for the cellulose to methyl levulinate process.